A before‐and‐after assessment of patch‐burn grazing and riparian fencing along headwater streams. Issue 5 (4th June 2016) - Larson, Danelle M.; Dodds, Walter K.; Whiles, Matt R.; Fulgoni, Jessica N.; Thompson, Thomas R.
Summary: Fire and grazing are common in grasslands world‐wide to maintain grass cover and cattle production. The effects of fire, cattle grazing and riparian fencing efficacy on prairie stream ecology are not well characterized at catchment scales. We examined alterations to stream water quality and biology from patch‐burn grazing (PBG) in tallgrass prairie during a five‐year, replicated, catchment scale experiment that used a Before‐After/Control‐Impact (BACI) design and was analysed by mixed‐effects models. Treatments included two patch‐burned control catchments (fire but no grazers) and PBG in two riparian‐fenced and two unfenced catchments. We assessed the effectiveness of riparian fencing for mitigating potential water quality impacts by monitoring water quality and riparian usage by cattle via Global Positioning System. Riparian fences effectively excluded cattle; however, in unfenced pastures, cattle aggregated along streams 10–20% of the grazing season. After initiation of PBG, we detected large increases in some nutrients, Escherichia coli, algal biomass, primary productivity and community respiration in all catchments with PBG. Some water quality variables, such as E. coli concentrations, recovered quickly after cattle were removed from pasture, which indicated resiliency. Riparian fencing moderately reduced the impacts to stream variables, indicating either overland flow and/or subsurface flow allowed nutrients and bacteria to enter the streams. Synthesis and applications . Patch‐burn grazing is a measurable disturbance that can alter the ecological condition of streams. Riparian fencing lessened the degree of impact, yet some water quality variables still exceeded regional reference conditions. Managers will need to assess the costs of riparian fencing compared to the moderate benefits that fencing provides to water quality. Abstract : Patch‐burn grazing is a measurable disturbance that can alter the ecological condition of streams. Riparian fencing lessened the degree of impact, yet some water quality variables still exceeded regional reference conditions. Managers will need to assess the costs of riparian fencing compared to the moderate benefits that fencing provides to water quality.